Arabic Learning Strategies In Madrasah Aliyah - Tribudiarti, Arum; Aqila; Aulia, Ashrafah Alaifhi (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
A learning strategy is a method, steps, tactics, or a design that will be used by teachers in the learning process, in order to achieve learning objectives, namely increasing students' understanding and improving students' cognitive abilities. In the Arabic language learning strategy, of course the objectives of learning Arabic are; Firstly, so that students can read and understand the Al-Quran and the hadiths of the Prophet, Arabic books, Arabic texts and the history of Islamic culture. Second, apart from learning, the aim of studying Arabic is to improve your skills in communicating in Arabic. Third, to increase your skills, interests and talents in Arabic. Therefore, the aim of this research is to find out what strategies are suitable to use in achieving the goals of learning Arabic. This research is qualitative in nature using literature study using descriptive analysis methods. The results of this research show that effective learning will create creative and active participants and improve students' cognitive abilities. Quality learning depends on the motivation, enthusiasm and creativity of an educator in the learning process, therefore an educator needs a strategy to achieve the desired goals. The strategies in learning Arabic are: (1) mufrodat learning strategy, (2) listening/istima' learning strategy, (3) reading/qira'ah learning strategy, (4) speaking/kalam learning strategy, (5) tarkib learning strategies, and (6) kitabah learning strategies.